Simple and Efficient Excitation Signals for Fast Impedance Spectroscopy - Ojarand, J.; Min, M. (Elektronika ir Elektrotechnika, 2013)
This paper deals with using of simple but energy efficient binary multififrequency excitation waveforms for fast bioimpedance spectroscopy. Binary waveforms can not only be generated in a simple way, but also the amount of useful excitation energy in these exceeds the energy of comparable sine wave based signals. This type of signals allows also versatile adapting (matching) of the shapes of the spectra of the object and excitation signal. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3468